Development of Science Learning E-Module with Online Media on Water Pollution Matter in Lake Tondano - Anggelina Jeujanan; Ferny Margo Tumbel; Ferdy Dungus (Edumaspul: Jurnal Pendidikan, 2024)
Water pollution in Lake Tondano is closely related to science subjects in junior high school on environmental pollution matter. This research aims to produce science learning e-modules on water pollution in Lake Tondano with online media that are feasible and effective. This type of development research refers to the Borg and Gall development model. Data collection techniques used interviews, questionnaires, and tests. The research instruments used interview sheets, product validation questionnaires, product practicality questionnaires, and learning outcomes tests. The results showed that: (1) the validity test by learning media experts obtained a score of 94%, included in the very valid category (no need for revision); (2) the validity test by material experts showed a score of 91% included in the very valid category (no need for revision); (3) limited trials in small groups showed a score of 88% included in the very practical category; and (4) the average score of student learning outcomes of 77% included in the effective category. Based on the research that has been conducted, the science e-module with online media on water pollution material in Lake Tondano is declared feasible and effective for students to use.